American Civil Liberties Union of Northern California Honors Howard Watkins with Lola Hanzel Courageous Advocacy Award - Watkins, Howard::::::::: (1987)
Nancy Pemberton and American Civil Liberties Union of Northern California Executive Director Dorothy Ehrlich seated at headtable Luncheon at Sheraton Palace Hotel in San Francisco